Penggambaran Relief Cerita Pada Beberapa Candi Di Jawa Tengah Dan Timur (Makna Simbolis dan Edukatif) - Hari Lelono (Berkala Arkeologi, 2004)
In order to seek national identity and to improve morals, one way can be referred to from the cultural heritage of our own ancestors through historical and archaeological sources (relief). One of the important aspects in the relief that needs to be developed and disseminated is mainly the stories of fables and symbols that are implied in the puppet reliefs. The story of the fable is very good for providing educational guidance to children and parents so that they have good character and refer to the noble roots of their ancestors.